Flame-retarded biocomposites of poly(lactic acid), distiller's dried grains with solubles and resorcinol di(phenyl phosphate). (February 2016) - Ju, Yaqing; Liao, Fenghui; Dai, Xiu; Cao, Yu; Li, Jiawei; Wang, Xinlong
Abstract: The distiller's dried grains with solubles (DDGS) were treated by smashing and water washing processes. The treatment effects on DDGS were analyzed, and the results showed that the thermal stability and the hydrophobicity of DDGS were improved by the treatment processes. The flame retarded biocomposites of poly(lactic acid) (PLA) with DDGS and degradable polymeric flame retardant resorcinol di(phenyl phosphate) (RDP) were prepared. The prepared biocomposites had good mechanical properties and the tensile strength of the biocomposite containing 15 wt% RDP and 15 wt% DDGS reached approximately 53 MPa. Meanwhile, using the limited oxygen index (LOI) and the underwriters laboratory (UL-94) tests, for the biocomposite, the LOI value was approximately 27.5% and V-0 rating in UL-94 was attained. Furthermore, the peak heat release rate of this biocomposite was reduced to 275 kW/m 2 compared with 310 kW/m 2 for pure PLA. After burning of the biocomposites, compact and coherent charred layer was formed and the char residues were analyzed in detail.